The Relationship between Childhood Traumatic Experiences and Social Anxiety Disorder Mediated by Cognitive Emotion Regulation in University Students - Zadfallah Farshami, Hanieh; Roshandel, Azam (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aimed to investigate the relationship between childhood traumatic experiences and social anxiety disorder (SAD) among university students, with a specific focus on the mediating role of cognitive emotion regulation (CER). Methodology: A cross-sectional design was employed, involving 367 university students from Islamic Azad University, Lahijan, Iran, during the academic year 2023-2024. Data were collected using validated self-report measures, including the Childhood Trauma Questionnaire (CTQ), the Cognitive Emotion Regulation Questionnaire (CERQ), and the Social Phobia Inventory (SPIN). Structural equation modeling (SEM) was used to analyze the direct and indirect effects of childhood trauma on SAD, with CER as a mediating variable. Findings: The results indicated a significant positive relationship between childhood traumatic experiences and SAD. Furthermore, CER was found to play a significant mediating role in this relationship, with maladaptive CER strategies, such as rumination and self-blame, exacerbating the effects of childhood trauma on SAD. Conversely, adaptive CER strategies, such as positive reappraisal and acceptance, were found to mitigate the impact of childhood trauma, reducing the severity of SAD symptoms. Conclusion: The findings highlight the critical role of CER in mediating the relationship between childhood trauma and SAD. These results suggest that interventions targeting CER strategies may be particularly effective in reducing social anxiety symptoms in individuals with a history of childhood trauma. The study underscores the importance of early intervention and culturally sensitive approaches in treating SAD among university students.